Pemanfaatan Potensi Lahan Dengan Mengoptimalkan Toga (Tanaman Obat Keluarga) Dikelurahan Bambu Kuning - Ababil Ferrel Salsabila; Salim Dinul Fitria Nur; Ilham Ilham; Nasihah Zumrotun; Sunaini Sunaini; Angraina Diah (Jurnal Pengabdian UntukMu NegeRI, 2022)
One of the UMRI group 21 KKN activities carried out was the planting of TOGA, the widespread spread of COVID-19 spurred residents to increase their immunity. This activity aims to increase public understanding of COVID-19 prevention efforts using TOGA. The method of implementation is direct practice, the activities are carried out in RW 09, Bamboo Kuning Village, Tenayan Raya sub-district. The result achieved is the increased understanding of citizens about efforts to prevent covid-19 by using TOGA.